With or without super platforms? Analyzing online publishers’ strategies in the game of traffic - Salminen J.; Maslennikov D.; Jansen B.; Olkkonen R. (My University, 2022)
Given the dominance of online platforms in attracting consumers and advertisers, online publishers are squeezed between declining traffic and advertising revenues from their website content. In turn, super platforms, the dominant content dissemination platforms, such as Google and Facebook, are monetizing online content at the expense of publishers by selling ad impressions in advertising auctions. In this work, we analyze publishers’ possibilities of forming a coalition and show that, under a set of assumptions, the optimal strategy for publishers is cooperation against a super platform rather than posting content on the super platform. Not choosing to publish on a super platform can yield the whole coalition more traffic, enabling some individual publishers to recoup the lost traffic. We further show that if the coalition does not forbid diversification, most publishers choose both coalition and super platform.
Social Informatics : 10th International Conference, SocInfo 2018, St. Petersburg, Russia, September 25-28, 2018, Proceedings, Part II